2018
DOI: 10.1007/s10048-018-0540-1
|View full text |Cite
|
Sign up to set email alerts
|

In vitro efficacy of ARQ 092, an allosteric AKT inhibitor, on primary fibroblast cells derived from patients with PIK3CA-related overgrowth spectrum (PROS)

Abstract: Postzygotic mutations of the PIK3CA [phosphatidylinositol-4,5-bisphosphate 3-kinase catalytic subunit alpha] gene constitutively activate the PI3K/AKT/mTOR pathway in PIK3CA-related overgrowth spectrum (PROS) patients, causing congenital mosaic tissue overgrowth that even multiple surgeries cannot solve. mTOR inhibitors are empirically tested and given for compassionate use in these patients. PROS patients could be ideal candidates for enrolment in trials with PI3K/AKT pathway inhibitors, considering the “clea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
68
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(68 citation statements)
references
References 47 publications
(79 reference statements)
0
68
0
Order By: Relevance
“…This documented overactive PI3K‐AKT pathway opens the option to potential additional therapeutic alternatives targeting this pathway for individuals with KOGS in addition to PDGFRB inhibitors (Pond et al, ). Treatments aimed at blocking downstream AKT signaling have been documented to inhibit this pathway in a dose‐ and time‐dependent manner in cells derived from individuals with activating mutations of PIK3CA and currently undergoing clinical trials in patients with PIK3CA‐related overgrowth spectrum (Ranieri et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…This documented overactive PI3K‐AKT pathway opens the option to potential additional therapeutic alternatives targeting this pathway for individuals with KOGS in addition to PDGFRB inhibitors (Pond et al, ). Treatments aimed at blocking downstream AKT signaling have been documented to inhibit this pathway in a dose‐ and time‐dependent manner in cells derived from individuals with activating mutations of PIK3CA and currently undergoing clinical trials in patients with PIK3CA‐related overgrowth spectrum (Ranieri et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…ARQ092 (miransertib) is a new allosteric inhibitor of AKT that is orally bioavailable and has a manageable safety profile in patients with advanced solid tumors. Studies using fibroblasts from PROS patients showed that ARQ092 had good antiproliferative activity and has now been granted “Fast Track” designation by the Food and Drug Administration for the treatment of PROS as well as Rare Pediatric Disease designation for the treatment of Proteus syndrome…”
Section: Discussionmentioning
confidence: 99%
“…21 The mTOR inhibitor sirolimus (rapamycin) has been used to treat KLA patients with a partial response in KLA patients. 2 24 and has now been granted "Fast Track" designation by the Food and Drug Administration for the treatment of PROS as well as Rare Pediatric Disease designation for the treatment of Proteus syndrome. 25 Based on this promising background, we thought that it might be beneficial to evaluate this new drug in cells from KLA patients to generate data of preclinical interest since these cells have hyperactive AKT.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it can provide clues for an underlying hereditary condition due to a germline mutation. In addition, increased knowledge of pathogenic mutations present in these lesions can stratify patients for targeted therapeutic options . A comprehensive and sensitive analysis is required because of the spectrum of genes involved and the mosaicism with low levels of mutated cells and also combined mutations.…”
Section: Resultsmentioning
confidence: 99%